Three essays on Global bank branches - Noh, Yoocheol (2022)
This thesis consists of three essays on the branches of global banks, which are the basic units of the global banking system and have significant implications for the financial stability of each country. To date, the branches of global banks have not received much attention in the literature. However, when we focus on their distinctive characteristics and linkages with local banks, it leads us to important narratives about cross-border capital flows, financial stability, and macroprudential policy.